Postgraduate Programs: Vision and perception in the Universidad Pedagógica y Tecnológica de Colombia (UPTC) - Torres Cruz, Doris Lilia; Prieto Ortega, Jinny Fernanda (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article aims at socializing the partial results of a research project entitled to read and to write the graduate development with a language of social responsibility, recorded in the General Research System with the number 1289. Identifying the undergraduate and postgraduate students’ perceptions face the postgraduate programs in the Faculty of Educational Sciences. This allows to point out the relevance of the procedures implemented through the educational policy and institutional regulations. The research is assumed from a historical and hermeneutic perspective, through this there is a diachronic process in the creation of postgraduate programs in the faculty of Sciences of Education-UPTC (Universidad Pedagógica y Tecnológica de Colombia). This University as one of pioneers in the teachers development in the country. Therefore, it has a mixed approach of qualitative and quantitative analysis of found data. In a first step, the findings of the pilot survey; then, the analysis to the surveys of students of the undergraduate programs; for in a third time, describe their perceptions of graduate students from the same faculty. Finally, conclusions are presented in front of the processes of the postgraduate level, its policy of internationalization, research and links with the secondary and technical education, along with the transfer of knowledge with the criteria of quality and social equity.